Green synthesis of silver nanoparticles mediated by anamorphic fungi and antibacterial and antifungal efficacy - Gomes, Dib Mady Diniz; Durán, Nelson; Seabra, Amedea Barozzi; Silva, Larissa de Paiva; Prado, Fabiano Brito; Silva, Taciana de Amorim; Teixeira, Maria Francisca Simas (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The aim of the present study was to investigate the effect of pH, temperature and silver nitrate (AgNO3) concentration on the synthesis of silver nanoparticles (AgNPs) by Aspergillus flavo-furcatis and to evaluate its antimicrobial activity. A full factorial experiment 2³ was carried out in order to assess the effect of physicochemical conditions on AgNP synthesis. The characterization of AgNPs was done through UV-Vis and ICP-MS spectroscopy. The antimicrobial activity was assessed by agar well diffusion and broth microdilution. pH and AgNO3 concentration had significant effects on the AgNP synthesis under experimental conditions. AgNPs synthetized at pH 9,0 and 1,5 mM AgNO3 showed increased efficacy against Staphylococcus aureus (3,17 μg/mL), Escherichia coli (6,35 μg/mL) and Candida albicans (0,79 μg/mL). These data support that AgNP synthesis by A. flavo-furcatis is influenced by pH and by AgNO3 concentration, suggesting that AgNPs have antimicrobial activity against S. aureus, E. coli e C. albicans.
Keywords: Amazon; Aspergillus; Antimicrobial activity; Mycosynthesis